2021
DOI: 10.1038/s41586-021-03720-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monoclonal antibody efficacy against SARS-CoV-2 variant strains

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
203
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(217 citation statements)
references
References 46 publications
11
203
3
Order By: Relevance
“…Additional mutations within the receptor-binding site (K417N and E484K) changed the amino acid sequence of the epitope and may contribute to the escape from antibody binding. Thus, a higher vaccine-induced antibody titer or neutralizing antibodies of higher affinity are needed to compete for the RBD N501Y –ACE2 interaction ( Chen et al, 2021 ; Focosi and Maggi, 2021 ). This will make the current vaccine less effective against SARS-CoV-2 variants that contain the N501Y mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Additional mutations within the receptor-binding site (K417N and E484K) changed the amino acid sequence of the epitope and may contribute to the escape from antibody binding. Thus, a higher vaccine-induced antibody titer or neutralizing antibodies of higher affinity are needed to compete for the RBD N501Y –ACE2 interaction ( Chen et al, 2021 ; Focosi and Maggi, 2021 ). This will make the current vaccine less effective against SARS-CoV-2 variants that contain the N501Y mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Lethal CNS invasion, combined with the absence of severe pulmonary hallmarks associated with lethal COVID-19, therefore calls for attentive caution when utilizing the K18-hACE2 mouse model to investigate certain aspects of SARS-CoV-2 pulmonary pathogenesis. Furthermore, due to the acute and fulminant neuroinvasion of this model, the protective ability of anti-viral therapies and T-cell based vaccines against lethal challenge in this model might indeed be underestimated, which is reflected in several studies that have utilized terminal timepoints proceeding neuroinvasion as their efficacy endpoints (5860). Regardless, the K18-hACE2 mouse model represents a promising model for understanding the mechanisms governing SARS-CoV-2 neuroinvasion, ACE2-independent virus entry, and evaluating potent and fast-acting prophylactic countermeasures.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these nanobodies make contacts with sites of circulating variants K417, L452 and E484, our results showed that these positions can be quite tolerant to mutations (Supporting Information, Figure S4). Interestingly, mutations L452R and T478K of B.617.2 lineage that can induce escape to neutralizing antibodies targeting the NTD and RBD 63, 64 resulted in relatively moderate binding energy losses for the biparatopic nanobody (Figure 5C,D). This is consistent with the observed effectiveness of the nanobodies against these antigenic variants.…”
Section: Resultsmentioning
confidence: 99%
“…61, 62 Highly transmissible SARS-CoV-2 variants with the increased affinity for ACE2 were discovered in lineage B.1.617 that encodes for mutations L452R, T478K, E484Q, D614G and P681R as well as B.1.618 lineage with mutations Δ145-146, E484K and D614G. 63, 64 The B.617.2 variant with L452R and T478K can induce a significant escape to neutralizing antibodies targeting the NTD and RBD, and polyclonal antibodies elicited by previous SARS-CoV-2 infection or vaccination. Nanobody and antibody mixtures targeting non-overlapping epitopes on the RBD have shown promise in preventing occurrence of resistance mutations.…”
Section: Introductionmentioning
confidence: 99%